Rodent Models of Spondyloarthritis Have Decreased White and Bone Marrow Adipose Tissue Depots - Furesi, Giulia; Fert, Ingrid; Beaufrère, Marie; Araujo, Luiza M.; Glatigny, Simon; Baschant, Ulrike; von Bonin, Malte; Hofbauer, Lorenz C.; Horwood, Nicole J.; Breban, Maxime; Rauner, Martina (Frontiers in Immunology, 2021)
Bone marrow adipose tissue (BMAT) has recently been recognized as a distinct fat depot with endocrine functions. However, if and how it is regulated by chronic inflammation remains unknown. Here, we investigate the amount of BMAT in HLA-B27 transgenic rats and curdlan-challenged SKG mice, two well-established models of chronic inflammatory spondyloarthritis (SpA). Subcutaneous and gonadal white adipose tissue and BMAT was reduced by 65-70% and by up to 90% in both experimental models. Consistently, B27 rats had a 2-3-fold decrease in the serum concentrations of the adipocyte-derived cytokines adiponectin and leptin as well as a 2-fold lower concentration of triglycerides. The bone marrow of B27 rats was further characterized by higher numbers of neutrophils, lower numbers of erythroblast precursors, and higher numbers of IL-17 producing CD4+ T cells. IL-17 concentration was also increased in the serum of B27 rats. Using a cell culture model, we show that high levels of IL-17 in the serum of B27 rats negatively impacted adipogenesis (-76%), an effect that was reversed in the presence of neutralizing anti-IL-17 antibody. In summary, these findings show BMAT is severely reduced in two experimental models of chronic inflammatory SpA and suggest that IL-17 is involved in this process.